The Impact of Some Pharmaceutical Marketing Strategies on Increasing Pharmacy Sales - Al-Burati, Ahmed Aref; Al-Zamani, Ahmed Ali Saleh; Awhaj, Osama Mohammed Abdulrahman; Ahmed, Islam Ahmed Mahyoub; Abdullah, Bashar Kamel Ahmed; Wasil, Sulaiman Ahmed Rashed (University of Science and Technology, Sana’a, 2026)
The research aimed primarily to determine the impact of pharmaceutical marketing strategies on increasing pharmacy sales in Al-Hawban. Six pharmaceutical marketing strategies were employed: customer loyalty, buy-one-get-one-free offers, time-based promotions, psychological pricing, category offers, and quantity offers. The study population consisted of pharmacies operating in Taiz city – Al-Hawban district. A purposive sampling method was used, selecting 12 pharmacies from Al-Hawban, Taiz Governorate: Dar Al-Dawa, Al-Awdi, Baghdad, Mecca, Bank Al-Dawa, Al-Taawun, Al-Mahdi, Al-Ittihad, Al-Abed, Akram Pharma, Bin Hussein, and Ayman Pharma. The strategies were implemented between November 6 and December 6, 2025. The research utilized a descriptive-analytical approach, combining quantitative data (sales statistics) with qualitative data. The research concluded with a set of results, the most important of which is: The combined impact of pharmaceutical marketing strategies on the sales volume of the pharmacies under study operating in Taiz Governorate, Al-Hawban, reached (55%), and it exceeded the target percentage of the research, which was (10%), which indicates that the application of pharmaceutical marketing strategies was highly affected in increasing the sales volume of the pharmacies under study.